When to Perform a Pancreatoduodenectomy in the Absence of Positive Histology? A consensus statement by the International Study Group of Pancreatic Surgery (ISGPS) - CONLON, KEVIN (My University, 2014)
Pancreatoduodenectomy (PD) provides the best chance for cure in the treatment of patients with localized pancreatic head cancer. In patients with a suspected, clinically resectable pancreatic head malignancy, the need for histologic confirmation prior to proceeding with PD has not historically been required, but still remains controversial. Methods An international panel of pancreatic surgeons working in well-known, high-volume centers reviewed the literature and worked together to establish a consensus on when to perform a pancreatoduodenectomy in the absence of positive histology. Results The incidence of benign disease after PD for a presumed malignancy is 5-13%. Diagnosis by ERCP brushings and percutaneous fine needle aspiration (FNA) are highly specific but poorly sensitive. Aspiration biopsy guided by endoscopic ultrasonography (EUS) has greater sensitivity, but it is highly operator-dependent and increases expense. The incidence of autoimmune pancreatitis (AIP) in the benign resected specimens is 30-43%. EUS-guided trucut biopsy, serum levels of IgG4, and HISORt (Histology, Imaging, Serology, Other organ involvement, and Response to therapy) are used for diagnosis. If AIP is suspected but not confirmed, the response to short course of steroids is helpful for diagnosis. Conclusions In the presence of a solid mass suspicious for malignancy, consensus was reached that biopsy proof is not required before proceeding with resection. Confirmation of malignancy, however, is mandatory for patients with borderline resectable disease to be treated with neo-adjuvant therapy prior to exploration for resection.. When a diagnosis of AIP is highly suspected, a biopsy is recommended, and a short course of steroid treatment should be considered if the biopsy does not reveal features suspicious for malignancy
PUBLISHED
Keywords: Pancreatoduodenectomy; pancreatic cancer